Ligand-dependent nano-mechanical properties of CdSe nanoplatelets: calibrating nanobalances for ligand affinity monitoring. Issue 18 (4th May 2021) - Martinet, Quentin; Baronnier, Justine; Girard, Adrien; Albaret, Tristan; Saviot, Lucien; Mermet, Alain; Abecassis, Benjamin; Margueritat, Jérémie; Mahler, Benoît
Abstract : The influence of ligands mass on the low frequency vibration of cadmium selenide colloidal nanoplatelets of different thicknesses is investigated using resonant low frequency Raman scattering. Abstract : The influence of ligands on the low frequency vibration of cadmium selenide colloidal nanoplatelets of different thicknesses is investigated using resonant low frequency Raman scattering. The strong vibration frequency shifts induced by ligand modifications as well as sharp spectral linewidths make low frequency Raman scattering a tool of choice to follow ligand exchange as well as the nano-mechanical properties of the NPLs, as evidenced by a carboxylate to thiolate exchange study. Apart from their molecular weight, the nature of the ligands, such as the sulfur to metal bond of thiols, induces a modification of the NPLs as a whole, increasing the thickness by one monolayer. Moreover, as the weight of the ligands increases, the discrepancy between the mass–load model and the experimental measurements increase. These effects are all the more important when the number of layers is small and can only be explained by a modification of the longitudinal sound velocity. This modification takes its origin in a change of the lattice structure of the NPLs, that reflects on their elastic properties. These nanobalances are finally used to characterize ligand affinity with the surface using binary thiol mixtures, illustrating the potential of low frequency Raman scattering to finely characterize nanocrystal surfaces.